Extracorporeal CO2 removal in a COPD patient with hypercarbic respiratory failure - GÜL, FETHİ (My University, 2023)
Introduction: Extracorporeal carbon dioxide removal (ECCO2R) is a respiratory support technique that provides only decarboxylation with low blood flow (0.3-1.0 L/min) without making a significant difference in blood oxygenation. In this report, we planned to present our clinical experience with ECCO2R in a patient who developed hypercarbic respiratory failure due to exacerbation of chronic obstructive pulmonary disease (COPD).Case: A 74-year-old male patient with hypertension and diabetes, who used a BiPAP device and oxygen concentrator at home due to COPD, presented to the emergency department with shortness of breath and respiratory distress. During the follow-up, the patient who had a hypercapnia and admitted to the intensive care unit (ICU). The VV-ECCO2R (multi ECCO2R ®-Fresenius Medical Care) was started on the 3rd day of hospitalization for the patient who needed NIMV for an average of 16-18 hours per day and remain hypercarbic despite NIMV support. The extracorporeal blood flow was set at 200 mL/min and maintained stable, while the sweep gas flow was adjusted to be 3-5 L/min according to the PCO2 value. The patient was followed with high flow oxygen support without need for NIMV from beginning of the ECCO2R. The patient, whose hypercarbia regressed, was weaned from ECCO2R at the 40th hour (Table 1). The oxygen support was maintained with a simple face mask and he was transferred to the service on the 13th day of hospitalization.Discussion: Current evidence regarding the use of ECCO2R in patients with obstructive diseases remains limited. Patient selection, type of ECCO2R device used and anticoagulation strategy seem important in order to benefit from ECCO2R. In our patient with severe exacerbation of COPD, we decided to treat the respiratory acidosis by removing CO2 with an artificial lung. The use of ECCO2R allowed avoiding intubation and invasive mechanical ventilation and finally he was discharged from the ICU.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Extracorporeal carbon dioxide removal; chronic obstructive pulmonary disease; ECCO2R; COPD